METHODS OF METOPROLOL ANALYSIS IN DRUGS AND BIOLOGICAL FLUIDS: REVIEW AND SUGGESTIONS - Horyn, M. M.; Logoyda, L. S. (International Journal of Medicine and Medical Research, 2020)
Background. Analytical method is increasingly implemented into fundamental pharmaceutical chemistry and analysis, considering their high sensitivity, accuracy, specificity and expressiveness. Objective. Metoprolol’s analytical method development was the research goal. Methods. The sources were world recognized journals (1990-2019) and key words used as filter were “metoprolol”, “spectrophotometry” “high-performance liquid chromatography, HPLC”, “quantitative analysis”, “validation”. Results. Chromatographic methods of analysis have the highest specificity and objectivity and allow qualitative and quantitative determination of Active Pharmaceutic Ingredient (API) in combined dosage forms and biological fluids without prior components separation. The main disadvantage of the described API analysis methods is long terms from the beginning of chromatography to API release and specific solvents used as the mobile phase in HPLC. New methods development and selection such chromatographic conditions that provide high speed and high efficiency at lower pressure of the system are essential. Also, the reduction of analysis time is achieved by simplifying the conditions for sample preparation. Conclusions. Analysts are constantly working on developing new analysis methods and their optimization in order to save time and consumables, which also ensures the efficiency of the developed method. There is no monograph on the substance or dosage forms of metoprolol in SPhU. Therefore, some of the developed methods should be suggested for the SPhU monograph, which is important for ensuring pharmacopoeial quality control of medicines in Ukraine.